STRATEGI DIGITALISASI DALAM PENGEMBANGAN POTENSI UMKM DESA LEBAKREJO, KECAMATAN PURWODADI - Moh Hatta; Dita Nisaul Hidayah; Dwi Astarina Widya Kinanti; Lailatus Syafa'ah; Udmi Sayyidah; Muhammad Satrio Wibowo Zaki (ANALISIS, 2026)
The Community Service Program (KKN) of group 37 UIN Sunan Ampel Surabaya was carried out in Lebakrejo Village, Purwodadi District, Pasuruan Regency. This village has great potential in the field of MSMEs, especially in the production of processed foods such as banana chips, cassava chips, various market snacks, and traditional herbal medicines. However, MSME players in this village face several challenges, such as limited capital, low understanding of digital marketing, lack of product innovation, and unfulfilled business legality such as NIB and PIRT. Seeing these conditions, KKN students carried out empowerment using the Participatory Action Research (PAR) approach, which involves the community in the process of identifying problems and finding solutions. Several programs were implemented, including MSME mapping, digital marketing and FGD training, business digitization (creation of business accounts, Google Maps, Instagram), creation of business signboards, and provision of basic food supplies. The results of the activities showed that some MSME players began to be open to the use of technology and began to understand the importance of online promotion and product innovation. This program also opened up space for closer dialogue and mentoring between students and the community. Despite the limited implementation time, this activity made an initial contribution to encouraging village MSMEs to develop further, become more independent, and be ready to compete in a wider market.